Differences between male and female players in the sagittal plane biomechanics during volleyball spike landing - Hsieh, Y. -Y.; Huang, C. F. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to investigate the kinematics and kinetics differences between male and female players after a volleyball spike landing. Eight male and eight female university volleyball players were recruited to participate in this study. The kinematic and kinetic data were collected by ten Vicon cameras (300 Hz) and two force plates (1500 Hz). The Visual 3D software was used to analyze the kinematic and kinetic variables. The results indicated that male players exhibited greater peak hip flexion angle, hip range of motion and hip extensor moment compared with female players. Female players exhibited greater peak ankle dorsiflexion and ankle range of motion than male players. These differences demonstrated that male and female players performed different strategies during volleyball spike landing.